Hypoglycemic effect of Camellia chrysantha extract on type 2 diabetic mice model (Bangladesh Journal of Pharmacology, 2017)
The aim of this study was to investigate the hypoglycemic effect of Camellia chrysantha using type 2 diabetic mice model. The ethyl acetate/dichloromethane extract exhibited the most effective hypoglycemic effect. Compared to model group, all the three groups of C. chrysantha extracts significantly improved the mices behavioral performance, weight, reduced water and food intake. The ethyl acetate/dichloromethane extract of C. chrysantha significantly reduced the blood glucose level in the first week after administration and the crude extract also showed a significant effect after longer time administration. All the three extracts reduced the fasting blood glucose level to a certain extent and ethyl acetate/dichloromethane extract exhibited most significant effect among all the three extracts.Video Clip of Methodology:1 min 31 sec   Click to watch